Influence of water vapour on the oxidation behaviour of a conventional aluminide and a new thermal barrier coating system sintered from a slurry. Issue 2 (2nd July 2013) - Brossard, M.; Bouchaud, B.; Pedraza, F.
<x xml:space="preserve">Abstract</x> In this work, the effect of water vapour on a new thermal barrier coating system synthesised from a slurry containing Al microparticles was studied under isothermal regime at 1100 °C for short oxidation times (50 h). Both dry air and argon gas atmospheres were investigated with increasing water vapour contents (0, 5, 10% RH, relative humidity) and the oxidation mechanisms and growth kinetics of the oxide scales were compared to conventional aluminide coatings up to 50% RH. The phase transformations occurring in the coating were characterised by local Raman micro‐spectrometry with complementary analytical techniques (X‐ray diffraction and FEG‐ESEM/EDS). The results demonstrated that water vapour does not exert a great influence on the oxidation of this type of coatings once an α‐Al2O3 scale is stabilised after an appropriate sintering of the coating. In contrast the combined effect of water vapour and oxidation onto oxide scales grown from raw aluminide coatings was shown to trigger delayed transformation of θ into α‐Al2O3, the appearance of pores and spallation, in particular in air + x %RH.